(untitled) (Fiep Bulletin - online, 2016)
Sculptural and functional mapping of Contractile Cells Mater is an unprecedented study of a small population of ten units of cells that are always working on staff and peer completely independently. It is an organized team, rational, accurate, consistent and highly specialized. Act in ten systems in the body, but this article only covers three systems; Immune, Heart and Genetics. They have an extraordinary ability to make an optical reading about everything and everyone around us up to ten generations and that accounts for every command and every vital action in our body; in muscle contractions, nerve synapses, reflex movements, systole, diastole, immunity and gas exchange, action potential, in short, all forms of actions which are involved vital functions in our body. They act in ten systems in the body, but this study reference will be made only to the three systems; cardiac, immune and genetic. This study, behind new concepts, not yet known in the scientific community, where by mapping coding, we know precisely which macrophage is our greatest enemy and antigen, is most responsible for cleaning our body, but they are under attack constant because they have an extraordinary capacity for memorization. We can also know through this article, that DNA does not exist as it is not acid RNA in the same way. Both are deoxyribose and must be called by DN and RN. We know what a JokeR-Deltha child or genius, which has the contemplation of two consecutive grandparents according to the mapping. We also know that heart is not a pump nor has three types of muscle as the authors say, but a muscle that has atrial cubes. We know purkinje the cell responsible for producing twins.